2022
DOI: 10.1186/s12967-022-03758-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule glycolysis inhibitor WZ35 exerts anti-cancer effect via metabolic reprogramming

Abstract: Background Liver cancer is the fifth leading cause of cancer death worldwide, but early diagnosis and treatment of liver cancer remains a clinical challenge. How to screen and diagnose liver cancer early and prolong the survival rate is still the focus of researchers. Methods Cell experiments were used to detect the effect of WZ35 on the colony formation ability and proliferation activity of hepatoma cells, nude mouse experiment to observe the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…The SLC2As have a strong correlation with cancer patient survival. For instance, SLC2A1 was found to be deleterious in LIHC, LUAD, PAAD, and SARC, this finding was similar across many databases and the majority of prior research [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. Also, we discovered that in LIHC and KIRC, improved OS was correlated with increased expression of SLC2A2.…”
Section: Discussionsupporting
confidence: 57%
“…The SLC2As have a strong correlation with cancer patient survival. For instance, SLC2A1 was found to be deleterious in LIHC, LUAD, PAAD, and SARC, this finding was similar across many databases and the majority of prior research [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. Also, we discovered that in LIHC and KIRC, improved OS was correlated with increased expression of SLC2A2.…”
Section: Discussionsupporting
confidence: 57%
“…EF24 has been documented to significantly suppress the growth of various tumors such as breast cancer, 53 ovarian cancer, 54 cervical cancer, 55 and gastric cancer 56 . WZ35 has shown significant inhibitory effects on gastric cancer, 57 liver cancer, 58 and breast cancer 38 . GO‐Y030 exhibits remarkable inhibition against colon cancer, 59 DMC inhibits the proliferation of renal cancer, while MHMM41 impedes the growth of human lung cancer cells 60 .…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory effect on autophagy of liver tumor cells is dependent on YAP1 ( 185 ). On the other hand, WZ35 reduces SLC2A1-mediated glycolysis by inhibiting YAP1, thus inhibiting the proliferation of liver tumor cells ( 186 ).…”
Section: Immunotherapy Strategy Of Targeting Yap1 For Liver Tumormentioning
confidence: 99%
“…WZ35 is a new curcumin derivative, which shows anti-tumor activity in gastric tumor, breast tumor, colon tumor and prostate tumor (219)(220)(221)(222)(223). Recent studies have found that WZ35 has inhibitory activity in liver tumor, and its mechanism is related to the down-regulation of YAP1 expression (185,186). On the one hand, WZ35 inhibits the growth of liver tumor cells by downregulating autophagy controlled through YAP1.…”
Section: Wz35mentioning
confidence: 99%